THE meaning of the fragment in Prosas apátridas (“STAT ELESS prose PIECES”) of JULIO RAM ÓN RIBEYRO - Gallegos, Oscar (2012)
Because of its fragmented and elusive nature, Prosas apátridas (“Stateless ProsePieces”) of Julio Ramón Ribeyro represents a real challenge to the theoreticaland hermeneutic understanding of literary criticism. This text of vital importancewithin the author’s whole work, has been delayed and not valued in its fairdimension due to biased or reductionist readings which only focuses on Ribeyro asa storyteller, or on texts that the author produced within the conventional genresof reception, leaving aside this peculiar work removed from these schemes. In thissense, this essay aims at developing a proper reading framework from which wecan understand the nature of the fragment in Prosas apátridas. For this purpose wepropose a theory of the fragmentary writing, we study the context of reception ofthe work and we link it to a Latin American tradition of fragmentary texts.